Pengaruh Mengikuti Program Kampus Mengajar terhadap Minat Menjadi Guru Pada Mahasiswa Pendidikan Matematika Untirta - Yolita Sofiatun Nufus; Maman Fathurrohman (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
The declining interest of millennial students and education students to become teachers needs attention. The importance of interest as a motivation for prospective teacher students to become professional teachers is the basis for the need to increase students' interest in becoming teachers. This study aims to determine the effect of the teaching campus program on interest in becoming a teacher and to find out the factors that support and or inhibit interest in becoming a teacher in Untirta Mathematics Education students participating in the teaching campus program. This research is a type of mixed method research using explanatory sequential design. The subjects in this study were Untirta Mathematics Education students participating in the teaching campus program from 1st to 4th year. The results showed that there was a positive influence of the experience of the campus teaching program on the interest in becoming a teacher in Untirta Mathematics Education students as indicated by a positive regression coefficient of 0.561. This means that every time there is an addition of one unit of the teaching campus program experience variable, the value of the interest in becoming a teacher variable increases by 0.561. This interest is supported by the factors of teaching campus program experience, feelings in teaching, attention to the quality of education, ideals, and family environment. Meanwhile, what hinders students in becoming teachers is mostly influenced by factors of professional perceptions and teacher welfare and social friend factors.